Pengaruh Kualitas produk, Persepsi Harga dan Media Sosial Terhadap Keputusan Pembelian Boost Juice Mall Kota Kasablanka - silviyanah; Hariadi Hadi Suwarno (Panorama Nusantara, 2022)
This This study examines how product quality, price perception and social media affect purchasing decisions at Boost Juice Mall Kota Kasablanka. By using accidental sampling technique with a sample of 100 respondents. Data analysis used multiple linear regression method with Statistical Package for the Social Sciences (SPSS). The results of this study indicate that social media and product quality have a beneficial and significant influence on purchasing decisions. While the price perception variable has a significant and negative effect on purchasing decisions